Investigation on the Hair Characteristics of Damascus and Kilis Goats - Sedat Behrem; Mahmut Keskin; Sabri Gul; Engin Unay; Muharrem Satilmis; Murat Unal; Yurdakul Sacli; Abdulkadır Erisek (Journal of Natural Fibers, 2022)
This study aimed to investigate the coarse outer guard hair and the fine down hair (cashmere) characteristics of Kilis and Damascus goats and to evaluate their potential for industrial use. Yearling goats, goats at first birth, second birth, and third birth were used as animal materials from Gaziantep. From the shoulder, rump, and rib areas of each goat, 20–25 g of the guard hair and the fine down hair (cashmere) samples were collected. These samples were examined in terms of diameter, length, tenacity, and elasticity at the Fleece and Mohair Laboratory of the International Livestock Research and Training Center. In the study, the average fiber diameter values were determined as 15.0 ± 0.08 and 15.1 ± 0.07 microns, and the fiber length values were 23.4 ± 0.38 and 22.4 ± 0.34 mm for Kilis and Damascus goats, respectively. In the light of these results, it can be said that the cashmere fiber diameter for both breeds is suitable for the textile industry. On the other hand, the fiber length is not long enough for the textile industry but can be evaluated by hand weaving method.